Pilot study of micromotion nailing for mechanical stimulation of tibial fracture healing - Hannah L. Dailey; Peter Schwarzenberg; Edmund B. Webb, III; Sinead A. M. Boran; Shane Guerin; James A. Harty (Bone & Joint Open, 2021)
Aims: The study objective was to prospectively assess clinical outcomes for a pilot cohort of tibial shaft fractures treated with a new tibial nailing system that produces controlled axial interfragmentary micromotion. The hypothesis was that axial micromotion enhances fracture healing compared to static interlocking. Methods: Patients were treated in a single level I trauma centre over a 2.5-year period. Group allocation was not randomized; both the micromotion nail and standard-of-care static locking nails (control group) were commercially available and selected at the discretion of the treating surgeons. Injury risk levels were quantified using the Nonunion Risk Determination (NURD) score. Radiological healing was assessed until 24 weeks or clinical union. Low-dose CT scans were acquired at 12 weeks and virtual mechanical testing was performed to objectively assess structural bone healing. Results: A total of 37 micromotion patients and 46 control patients were evaluated. There were no significant differences between groups in terms of age, sex, the proportion of open fractures, or NURD score. There were no nonunions (0%) in the micromotion group versus five (11%) in the control group. The proportion of fractures united was significantly higher in the micromotion group compared to control at 12 weeks (54% vs 30% united; p = 0.043), 18 weeks (81% vs 59%; p = 0.034), and 24 weeks (97% vs 74%; p = 0.005). Structural bone healing scores as assessed by CT scans tended to be higher with micromotion compared to control and this difference reached significance in patients who had biological comorbidities such as smoking. Conclusion: In this pilot study, micromotion fixation was associated with improved healing compared to standard tibial nailing. Further prospective clinical studies will be needed to assess the strength and generalizability of any potential benefits of micromotion fixation.